Pliny the Elder: Lessons from the Naturalist as an Early Neuroscientist. (April 2023) - Chu, Duong T.; Rosso, Mattia; Santoro, Jonathan D.
Pliny the Elder was a prolific Roman author, naturalist, and military leader. Yet, his impact on modern-day neuroscience, psychiatry, and neurology has been little explored. Here, we aimed to trace the origins of our current understanding of the brain in ancient Rome through Pliny and his work, Natural History . As his magnum opus, this 37-book tome catalogs the facts and observations of natural life collected by Pliny, reflecting the knowledge of his time. Following the cephalocentric school of thought, Pliny places the brain as an agent for consciousness and details its diseases. Further, we explore Pliny's methods, which allow him to build a thorough collection of clinical descriptions and remedies. This body of work serves as an important lesson for future neuroscientists on the power of observation, the role of the humanities, and the necessity of understanding the origin of modern scientific thinking.